Implementasi Algoritma Genetika Dalam Penjadwalan Jeda Iklan Pada Stasiun Radio 99.1 Most FM - Mutiah, Mutiah; Buulolo, Efori; Silalahi, Natalia (Forum Kerjasama Pendidikan Tinggi, 2020)
The screening of advertisements on a commercial radio station is done every day from Sunday to Saturday. In commercial radio stations, in general, making ad schedules is still manually which results in delays in the presentation of the weekly ad schedule. Playback time consists of two types, namely prime time and regular time. Radio Ad Scheduling that will be discussed in this study is the ad screening that is carried out on the radio broadcast schedule, which is between 5 am to 24 pm in which with the rules every 15 minutes are provided 3 ad playback slots with a maximum duration of 1 minute per ad. So if the radio broadcast time per day is 19 hours, then the maximum number of ads per day that can be displayed is 76 ads. Another rule is the implementation of prime time, the hours at which the general public (listeners) have the greatest opportunity to listen to the radio, which is between 6:00 and 10:00 in the morning and 16: 00-20: 00 at night. The number of screenings of the same advertisement on one day is limited to prime time which is 5 times, while for regular time is 8 times. The radio scheduling process is carried out using genetic algorithms consisting of chromosome initialization, selection, crossover and mutation processes. The chromosomes in this study consist of 3 genes, each chromosome will be evaluated based on its fitness value which is calculated based on the number of violations of rules that occur on each chromosome in an individual. Where rule 1 is the number of plays per advertisement that cannot be more than 5 times in a day and rule 2 is that there cannot be two or more ad scheduling shows on the same day and time. After that the fitness value of each chromosome is obtained, then the selection, crossover and mutation are carried out. From this research an optimal ad schedule is produced by scheduling overall ad data, day and time of ad playback